Interdisciplinarity in the context of Information Science: currents and questions - Santos Neto, Joao Arlindo dos [UNESP]; Santos, Juliana Cardoso dos [UNESP]; Teles, Paulo Sergio [UNESP]; Pomim Valentim, Marta Ligia [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2017)
This article investigates interdisciplinarity in the context of Information Science (CI), its concepts and characteristics from a literature review. It aims to elucidate the discussion of the theme and the approaches that have been used in studies; it also proposes an embryonic concept for interdisciplinarity. It analyzes the first studies by Lena Vania Pinheiro and confronts them with the latest researches. The study concludes that the CI, Library science and Computer science perform an interdisciplinary dialogue, that is, these areas interact and create knowledge or improve the existing, being useful and recognized by all the involved areas.
Keywords: Interdisciplinarity; Information Science; Complexity Theory